Tail coiling behaviour around conspecific’s body during fur rubbing in white-faced capuchins - Helene Meunier; Jean-Louis Deneubourg; Odile Petit (Revue de Primatologie)
Capuchins select certain plants to rub their pelage, a behaviour that can be both solitary, or collective. When rubbing their fur in body contact of conspecifics, capuchins sometimes coil their semi-prehensile tail around the body of the capuchin(s) in contact. However, the underlying mechanisms of tail coiling around conspecifics have never been studied previously and we propose to examine the impact of sociodemographic factors on this peculiar behaviour. Through this quantitative study, we found that (1) all the individuals emit and receive tail coiling, (2) affiliation drives the extent to which this behaviour is emitted; (3) emission and reception of tail coiling are symmetrical, even if delayed in time; (4) tail coiling frequency depends on the food resource used to perform fur rubbing and (5) tail coiling does not increase the duration of fur-rubbing behaviour. Our data does not support the hypothesis that tail coiling allows the recruitment of conspecifics in fur rubbing behaviour; instead, this behaviour seems to be more associated with social allo-rubbing.